Agronomic evaluation of cowpea as a function of weed control with herbicides and different combinations - Souza, Wando Wilson; Oliveira, Alexandre; Dutra, Alek; Nunes, Renato Leandro; Cavalcante, Robson (Revista Ciência Agronômica, 2016)
Cultivation of the cowpea is important in various regions of Brazil, but competition from weeds is one of the factors which limit productivity. The aim of this study therefore was to evaluate the pre-plant selectivity and efficiency of different herbicides, and combinations of herbicides, in the cowpea [Vigna unguiculata (L.) Walp.]. An experiment was carried out in a randomised block design, in lots split over time and with three replications, using a 4 x 7 factorial scheme, where the treatments consisted of: glyphosate, glyphosate + imazethapyr, glyphosate + flumioxazin, glyphosate + imazethapyr + flumioxazin, glyphosate + ready mix (imazethapyr & flumioxazin), and two control treatments (one with no weeding and one with manual weeding). The treatments were evaluated in combination with four different sowing times, i.e. immediately after application of the herbicides, and at five, ten and fifteen days after application (DAA). The combination of glyphosate + flumioxazin at 15 DAA, gave the highest mean productivity, 1,105.32 kg ha-1, followed by manual weeding with 1,027.37 kg ha-1. The herbicide mixtures of glyphosate + imazethapyr + flumioxazin caused phyto-toxicity in the cowpea crop, limiting the production components. The best strategies for weed control in this crop are manual weeding with seeding at 10 DAA, as well as the application of a glyphosate + flumioxazin mixture with seeding at 15 DAA.